Problematika Penyelesaian Sengketa Hak Cipta melalui Jalur Perdata: Disharmoni Normatif dan Tantangan Pembuktian dalam Rezim Undang-Undang Nomor 28 Tahun 2014 - Zhakiya Eka Mulya Fadhillah; Naswa Aulia Putri; Anggi Sri Haryati Simarmata (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the settlement of copyright disputes through civil law mechanisms under Law Number 28 of 2014 on Copyright, employing a normative juridical approach with statutory and doctrinal analysis. The research focuses on the coherence and synchronization of copyright norms with civil procedural frameworks, including the Civil Code, HIR, and RBg, in addressing disputes related to economic and moral rights. The findings reveal that Indonesia adopts a declarative system of copyright protection, granting automatic rights upon fixation, yet evidentiary challenges persist due to the absence of mandatory registration. Furthermore, the study identifies structural limitations in civil litigation, particularly in the assessment of damages, evidentiary standards, and enforcement of court decisions. Through interpretative legal methods, including grammatical, systematic, and teleological approaches, this research highlights the gap between normative expectations and practical implementation. The study concludes that strengthening institutional mechanisms, improving legal coherence, and adapting regulatory frameworks to digital contexts are essential to ensure effective dispute resolution and legal certainty in Indonesia’s copyright regime.